Pengaruh Penambahan Kitosan dan Gliserol Terhadap Karakteristik Film Bioplastik dari Pati Biji Nangka - Umi Ermawati; H Haryanto (Prosiding University Research Colloquium, 2020)
Plastic is one of important thing in daily life. The problems of conventional plastics are taking decades to degrade in nature and are produced by non-renewable sources like petroleum, coal and natural gas. Bioplastics have potential to reduce the problems of plastic waste because of the environmental friendly properties. Bioplastics are biodegradable plastic that made of renewable biomass such as starch, lignin, cellulose. Jackfruit seeds contain starch that can be used as the main ingredient of bioplastics with the addition of chitosan and glycerol to improve the mechanical properties of bioplastics. The aim of this research to obtain the effect of adding chitosan and glycerol in the making of jackfruit seed starch bioplastic films viewed from several parameters. Bioplastic was synthesized by dissolving jackfruit seed starch mixed with chitosan mass variation (1 g, 1.5 g, 2 g) and glycerol volume (15%, 35%, 55% (w / w) starch) at temperature of 70oC for 1 hour. Bioplastic sheets are tested for tensile strength, elongation at break (elongation) and biodegradation ability. The results showed that chitosan and glycerol gave an impact to mechanical properties and biodegradability. The best results of tensile strength on the addition of chitosan 1 gr and glycerol 15% (w / w starch) amounted to 9.12 MPa, the best %elongation in the addition of chitosan 1 gr and glycerol 55% (w / w starch) was 3.121% and the fastest degradation time on the addition of 1 gram chitosan and 15% (w / w starch) glycerol for 4 days.